Fungal Community Composition and Diversity Vary With Soil Horizons in a Subtropical Forest - Luo, Xia; Liu, Kezhong; Shen, Yuyu; Yao, Guojing; Yang, Wenguang; Mortimer, Peter E.; Gui, Heng (Frontiers in Microbiology, 2021)
Soil fungal communities, which drive many ecosystem processes, vary across soil horizons. However, how fungal communities are influenced by soil horizon layers remains largely unstudied. In this study, soil samples were collected from the organic horizon (O horizon) and mineral matter horizon (M horizon) in two sites of Dabie Mountain, China and the effects of the two horizons on the soil fungal community composition were assessed based on Illumina MiSeq sequencing. Our results showed that soil fungal community composition varied with soil horizons, and soil fungal species richness and diversity in the O horizon were significantly higher than that in the M horizon. Total organic carbon (TOC), total organic nitrogen (TON), Alkali-hydrolyzable nitrogen (AHN), available potassium (AK) and available phosphorus (AP) significantly influenced fungal community composition, abundance, and diversity across the two horizons (P<0.05). Furthermore, precipitation was found to have a significant effect on fungal community composition. Our results demonstrate changes in fungal communities across soil horizons and highlight the importance of soil organic matter on fungal communities and diversity.